Supply Chain Optimization at Minimarket Utama Mart Through an E-Procurement System - Ramadhana, Mochammad Sakti; Handayani, Wiwik (JURNAL MANAJEMEN MOTIVASI, 2025)
Utama Mart minimarket faces procurement inefficiencies due to unintegrated manual systems. This research aims to optimize the supply chain using an open-source ERP-based E-Procurement system, ERPNext. The system was developed using the Rapid Application Development (RAD) method and evaluated through the System Usability Scale (SUS) and User Acceptance Testing (UAT). Results showed significant efficiency gains: procurement time reduced by 79.2%, manual tasks by 76.9%, and tracking time by 90%. The SUS score reached 72 (good), while UAT acceptance rate was 69%. ERPNext proved effective and well-received in improving operational efficiency and supply chain integration in the retail sector.